Refleksi Psikologi Terhadap Bencana Gempa dan Tsunami Aceh - Fuad Nashori (Unisia, 2005)
At Aceh and North Sumatra, December 26, 2004, earthquake and tsunami happened cause many people died as victims, many houses destructed and losing wealth. Morte than 100 thousands of people died. At Nabire, Papua, February 7, 2004, at least 35 people became the victims of consecutive earthquake, those did at Padang Panjang Western Sumatra, 21 of February 2004. This article tries to describe the efforts how to overcome psychological conditions of earthquake victims and to incresase the preparation to help them. Those can be conducted based on psychological point of view.